Analysis of Marketing Strategy and Social Capital on the Performance of Batik MSMEs in Sidoarjo After-Covid-19 Pandemic - Krismawan, Alfaldo; Fauzi, Akhmad; Sukarno, Gendut (International Journal of Business and Applied Economics, 2024)
After-COVID-19 pandemic, MSMEs need to restructure strategies and overcome the impacts resulting from restrictions. Many of them experienced severe economic pressure due to mobility restrictions, decreased demand, and rapid changes in consumer behavior. The context of this research directs the researcher to focus on MSMEs engaged in the batik industry. The study will concentrate on marketing strategies and social capital as key factors influencing the performance of batik MSMEs. Adaptive and innovative marketing strategies, including the use of digital technology, become crucial in maintaining competitiveness. On the other hand, social capital, which encompasses networks, norms, and trust, can be valuable assets in facing challenges. This research will investigate how batik MSMEs implement marketing strategies and leverage social capital in dealing with the pandemic's impact. The population and sample in this study were the owners/leaders/managers of batik in Sidoarjo as many as 60 respondents. The analysis technique used in this research is SEM (structural equation model) - PLS (Partial Least Squares). The findings in this study indicate that marketing strategies have a positive effect on the performance of MSMEs, then social capital also has a positive effect on the performance of MSMEs, then marketing strategies affect innovation through performance and also social capital affects innovation through performance.